Review of the desalination and water purification technology roadmap (National Academies Press, 2004)
The Bureau of Reclamation and Sandia National Laboratories jointly developed the Roadmap to serve as a strategic research pathway for desalination and water purification technologies to meet future water needs. The book recommends that the Roadmap include a sharper focus on the research and technological advancements needed to reach the long-term objectives. The book also suggests that the environmental, economic, and social costs of energy required by increased dependence on desalination be examined. Strategies for implementing the Roadmap initiative are provided.